Project Managers’ Competencies in Managing the People Elements of Change within the United Arab Emirates - Al Falasi, Saoud Saif Ateeq (2017)
The aim of this research is to investigate the roles and competencies of project managers in managing change in the United Arab Emirates (UAE). The study focuses on people management. While some of the previous research argues that project managers are not effective managers of change, other studies, emphasize that they, in fact, are key players in managing change. These differing views are the main motivators for this research which aims to fill the gaps, clarify the issue and focus on its relevance in the UAE. In doing so, this research also aims to generate a better understanding of the role of project managers in managing change and the people involved in change. The objectives are also to shade some light the roles that project managers could play in promoting effective and successful change. In pursuing this research, we endorsed and adopted a research approach that is both qualitative and quantitative. The reason for using both approaches is because neither of these, alone, is sufficient to capture the key issues and provide answers to the main research questions being investigated. Hence data was collected using both interviews and survey questionnaires. We targeted project managers, including professionals and department managers serving a selected number of UAE organisations that have experienced major change in recent years. The main focus was to examine project managers’ roles in enhancing people’s commitment, participation, and motivation in the change process. In addition to this, and due to the importance of leadership and information management in change management, the project managers’ roles as leaders and as communicators was also considered. The study also looks at the role of project managers in managing stakeholders. To this end, we developed and explored two main research questions which translate into eight main hypotheses. The main findings of the study confirmed our hypotheses and revealed that there is no difference between the respondents’ ratings of the competencies needed for managing change initiatives. The findings also revealed that planning change competencies (PC1, PC2, PC5, EC1, EC2, MC1, MC2 and CC1) are associated with achieving the PM objectives. The study also found that evaluating the performance of change projects competencies (EPC2 and EPC7) is associated with achieving the PM objectives. The study also found that managing change projects competencies (MP1, MP2, MP3, MP5 and MP9) is significantly associated with achieving PM objectives. In addition, we also found that measuring the success factors competencies (PQC1, [viii] PQC2 and PQC5) is strongly associated with achieving the PM objectives. Regression analysis revealed that project managers’ performance in terms of achieving objectives is highly dependent on PC2, IC1, EC2, EPC1, EPC5, EPC6, EPC7, MP3, MP5 and PQC2. The above findings have significant practical implications. Based on these, and in order to minimize resistance to change, it is strongly recommended project managers are fully involved in planning activities right from the start. The responses of the project managers and the department managers revealed several activities embedded in the daily project management practices. Future study in this area would reveal more benefits of project managers’ reporting activity and would result in the highlighting of additions to reports related to people management. A future study may also investigate the reporting activity as part of the communication process.